Is floret primordia death triggered by floret development in durum wheat? - Ferrante, Ariel (Oxford University Press, 2013)
Survival of floret primordia initiated seems critical for the determination of grain number and yield in wheat, and understanding what determines floret mortality would help in the development of more robust physiological models of yield determination. The growth of the juvenile spikes has been frequently considered the determinant of grain number, implying that floret development would depend on resource availability and that the onset of floret death would be related to spike growth. However, this model has been recently challenged from a study concluding that floret death started when the most advanced floret primordia reached a particular developmental stage. As the few previous studies on this relationship involved photoperiod treatments which affect both floret development and the onset of spike growth, conclusions cannot be considered mechanistic. This comprehensive study analysed in detail floret development in wheat as affected by resource availability (mainly soil nitrogen levels) and found that the onset of floret death may occur when development of the most advanced florets ranged from stages 5 to 9 and that the average and standard deviation of floret developmental stage coinciding with the onset of floret death was not related to the level of availability of resources. These results provide further support to the model relating the onset of floret death with the initiation of active growth of the juvenile spike in which florets are developing.